Analysis of PV cell parameters of solution processed Cu-doped nickel oxide hole transporting layer-based organic-inorganic perovskite solar cells. (October 2020) - Khan, Firoz; Rezgui, Béchir Dridi; Kim, Jae Hyun
Graphical abstract: Highlights: A maximal value of Jph was obtained for Cu/Zn molar ratio of 5%. The value of Jph was increased with an increase in the annealing temperature. Rsh was increased with increase in annealing temperature. Rs was decreased with increase in annealing temperature. Both the n and J0 were increased with rise in annealing temperature. Abstract: The performance of an organic-inorganic perovskite solar cell (PSC) can be enriched via sinking the losses arisen in it. These losses are signified by the photovoltaic (PV) cell parameters (photogenerated current density ( Jph ), shunt resistance ( Rsh ), series resistance ( Rs ), diode ideality factor ( n ), and reverse saturation current density ( J0 )). In this paper, the dependency of the PV cell parameters of the Cu-doped nickel oxide (NiO:Cu)-based PSCs was investigated as a function of the Cu-doping ( RCu/Ni ) and the annealing temperature (tan ). The maximum value of Jph was obtained for RCu/Ni  = 5% and tan = 400 °C. Moreover, the Rsh value enhanced by increasing RCu/Ni and tan, while the Rs was decreased with the increase of the annealing temperature with the minimal value attained at RCu/Ni and tan of 5% and 400 °C, respectively. Both n and J0 increased with the rise in RCu/Ni and tan . Electrical measurements showed that PSC fabricated using 5% NiO:Cu-HTL annealed at 400 °C exhibits the highest PV performance with a short-circuit current density ( Jsc ) of 21.24 mA/cm 2, an open-circuit voltage ( Voc ) of 1.031 V, a fill factor ( FF ) of 72.50% and a power conversion efficiency ( η ) of 15.88%. The corresponding values of Jph, Rsh, Rs, n and J0 are 21.31 mA/cm 2, 1042.69 Ω.cm 2, 3.265 Ω.cm 2, 1.9739 and 3.025 × 10 −11 A/cm 2, respectively. These encouraging results provide the possibility to further optimize the optical and electrical properties of NiO:Cu-HTLs and pave the way for the development of more stable and highly-efficient PSCs.